The Transformation of Municipal Services: towards Quality in the Public Sector - Pablo Gutiérrez Rodríguez; José Luis Vázquez Burguete; Roge Vaughan; Jonathan Edwards (Theoretical and Applied Economics, 2009)
The development of the public service modernization seeks to facilitate services delivery to citizens, when and where they need them. For it, management and utilization of service quality have special relevancy. In this paper, we are trying to contribute for improving the relations between the small public local administrations and citizens across analysis of the link between quality and satisfaction, beside of analyzing how they relate to citizen’s credibility on institutions. By means of opinions spilt by citizens, obtained results allow us to raise a series of public policies and offers for the improvement of administration service quality, which end up as directly satisfaction and credibility.